2014
DOI: 10.1589/jpts.26.1779
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-myofascial Release on Reduction of Physical Stress: A Pilot Study

Abstract: [Purpose] This study aims to examined the effect of the self-myofascial release induced with a foam roller on the reduction of stress by measuring the serum concentration of cortisol. [Subjects and Methods] The subjects of this study were healthy females in their 20s. They were divided into the experimental and control groups. Both groups, each consisting of 12 subjects, were directed to walk for 30 minutes on a treadmill. The control group rested for 30 minutes of rest by lying down, whereas the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…[11][12][13] which increases arterial function, 14,15 through cortisol level's modulation. 16 With these results, we can conclude that in our study the muscular recovery is better after the application of the crossed hands technique.…”
Section: Citationsupporting
confidence: 67%
“…[11][12][13] which increases arterial function, 14,15 through cortisol level's modulation. 16 With these results, we can conclude that in our study the muscular recovery is better after the application of the crossed hands technique.…”
Section: Citationsupporting
confidence: 67%
“…Several studies have recently reported the effects of the FR on kinematic variables, such as sprint speed, the speed of changes in direction, and vertical jump [12,13]; the ROM [4,5,11,13]; mechanical responses such as isometric force, the rate of force development, and dynamic strength-endurance [4,5,12,13]; the characteristics of muscle activation via electromyography [5]; muscle soreness [12,13]; and even biological factors such as cortisol levels [16]. However, TMG has not been used to assess muscle mechanical properties after FRs treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the use of FRs on biological stress have also been studied. Kim et al [16] examined the effect of self-myofascial release -induced using a FR on the reduction in stress by measuring the serum concentration of cortisol. There was not a significant difference between the control and the experimental groups after the use of the FR on the spine, cervix, thorax, quadriceps, hamstring, tensor fascia latae or calf.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the slow, gentle and gradual stimulation of the fascia and the Ruffini endings within caused the subsequent activation of the parasympathetic nervous system, which, in turn, caused a decrease in blood pressure and pulse rate. 20 Kim et al 21 observed a decrease in cortisol (known as a stress hormone) levels following self-myofascial release and it was attributed to the suppression of the sympathetic nervous system through relaxation of the fascia. Therefore, it can be assumed that the relaxation of the fascia can cause activation of the parasympathetic nervous system and decrease blood pressure and pulse rate.…”
Section: Discussionmentioning
confidence: 99%